Left bundle branch pacing in third-degree atrioventricular block following morrow surgery: a case report - Huang, Keqiang; Gan, Hongmei; Jiang, Jingjing; Tang, Cheng (Frontiers in Cardiovascular Medicine, 2024)
Left bundle branch pacing (LBBP) has proven to be an alternative method for delivering physiological pacing to achieve electrical synchrony of the left ventricle (LV), especially in patients with atrioventricular block and left bundle branch block (LBBB). However, it is unclear whether it still achieved in patients whose left bundle branch (LBB) has had surgery-induced damage. The Morrow operation (Morrow septal myectomy) is regarded as one of the most effective treatments for hypertrophic obstructive cardiomyopathy (HOCM). The surgery resects small sections of muscle tissue in the proximal ventricular septum nearby or contains the LBB, which means that physical damage to the LBB is almost inevitable. Approximately 2%-12% of patients may need pacemaker implanted after Morrow surgery. LBBP is a feasible and effective method for achieving electric resynchronization of LBBB compared to right ventricular pacing (RVB). Nevertheless, there is a dearth of data on LBBP in third-degree atrioventricular block (AVB) following Morrow surgery. We report a case of successful LBBP in those patients.